ANALISIS BIOMASSA DAN CADANGAN KARBON BAMBU BELANGKE - Sehat Martua Pasarbu; Siti Latifah; Muhdi Muhdi (Program studi Kehutanan USU, 2016)
Bamboo is a group of plants that have the ability to absorb CO2 in high concentrations because having the number of stomata on bamboo leaves relatively tight and has are more than 500 stomata per mm2. Thus bamboo plant can be used as an effective bioakumulator which can reduce carbon emissions in the atmosphere. The purpose of this study was to determine the biomass content of bamboo, and (carbon stocks) in the public forests of bamboo and analyze the uptake of CO2 in bamboo plantations community forest Belangke (Gigantochloa pruriens Widjaja). The method used in this study is a destructive method. Sampling was done by purposive sampling felling. The results showed the best allometric equations for mass content of the biomass and carbon was W = 173.889-533.233D+4.262D2 for biomass content and C = 54.606-D-16.386+1.297D2 for carbon mass. The potential of biomass and carbon stocks in Forest Community Durin Serugun village, Sibolangit sub-district, Deli Serdang District is 16.59 tonnes / ha and 6.08 tons C / ha. Keywords: Biomass analisys, Carbon stock, Bambu belangke (Gigantochloa pruriens Widjaja), Community Forest, Desa Durin Serugun.